Managerial accounting : creating value in a dynamic business environment - Hilton, Ronald W. (New York : McGraw Hill Education, 2011)
The emphasis of Managerial Accounting, 9th edition is on teaching students to use accounting information to best manage an organization. In a practice Hilton pioneered in the first edition, each chapter is written around a realistic business or focus company that guides the reader through the topics of that chapter. Known for balanced examples of Service, Retail, Nonprofit and Manufacturing companies, Hilton offers a clear, engaging writing style that has been praised by instructors and students alike. As in previous editions, there is significant coverage of contemporary topics such as activity-based costing, target costing, the value chain, customer profitability analysis, and throughput costing while also including traditional topics such as job-order costing, budgeting and performance evaluation
1. The changing role of managerial accounting in a dynamic business environment -- 2. Basic cost management concepts and accounting for mass customization operations -- 3. Product costing and cost accumulation in a batch production environment -- 4. Process costing and hybrid product-costing systems -- 5. Activity-based costing and management -- 6. Activity analysis, cost behavior, and cost estimation -- 7. Cost-volume-profit analysis -- 8. Absorption and variable costing -- 9. Profit planning and activity-based budgeting -- 10. Standard costing, operational performance measures, and the balanced scorecard -- 11. Flexible budgeting and the management of overhead and support activity costs -- 12. Responsibility accounting, quality control, and environmental cost management -- 13. Investment centers and transfer pricing -- 14. Decision making: relevant costs and benefits -- 15. Target costing and cost analysis for pricing decisions -- 16. Capital expenditure decisions -- 17. Allocation of support activity costs and joint costs.
Includes index.
Keywords: MANAGERIAL ACCOUNTING